Customer Journey - How can customer journey be improved in the airline industry - Maniar, Rohen (2017)
The study presents the customer journey and the experience the passenger gets in an airline industry. Many studies explain the role of innovative brand experience in the airline industry but not on the journey and how can that be a competitive advantage to the airline. The goal of the study was to identify the key touchpoints and what are the difficulties or barriers a passenger's faces while travelling. The purpose of the paper is to understand how the customer journey can be improved in the airline's industry. A qualitative method for research was used as a part of the study. A minimum of 25 papers and 6 articles were read to identify the journeys and the hassle with it. The explanatory research was used to understand the journey. The results revealed that touchpoints that are not owned by the brand itself are the most difficult phase for the passenger and airlines have not focused on the entire journey cycle. On the basis of that, a recommendation has been given that airlines make their own process to make it less complex and go digital by navigating their passenger through the airport and to make the entire organisation customer-centric as the support team is as important as the front office team.